1975
DOI: 10.1159/000178700
|View full text |Cite
|
Sign up to set email alerts
|

Therapy-Orientated Diagnosis of Secondary Amenorrhoea

Abstract: A programme for investigation of secondary amenorrhoea is described, which is based upon a functional classification of the endocrine causes of anovulation. All diagnostic enquiries not directly yielding a therapeutic dividend are excluded from this protocol. Three main categories of amenorrhoea are recognised: primary ovarian disease, hyperprolactinaemia and disorders of gonadotrophin secretion. There are subdivisions of each category, each with its own special diagnostic and therapeutic implications. Initial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1977
1977
2010
2010

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(3 citation statements)
references
References 9 publications
1
2
0
Order By: Relevance
“…The hyperprolactinaemic patients had even higher responses of FSH and LH than healthy women in early follicular phase of the menstrual cycle. Normal or excessive gonado¬ trophin responses to LH-RH in hyperprolactinaemic patients have also been described by other investigators (Mortimer et al 1973;Jacobs et al 1975;Archer et al 1976). However, Bohnet et al (1976), who used the lower test dose of 25 /ig of LH-RH found impaired or absent responses in 12 of their 17 women with hyperprolactinaemia.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…The hyperprolactinaemic patients had even higher responses of FSH and LH than healthy women in early follicular phase of the menstrual cycle. Normal or excessive gonado¬ trophin responses to LH-RH in hyperprolactinaemic patients have also been described by other investigators (Mortimer et al 1973;Jacobs et al 1975;Archer et al 1976). However, Bohnet et al (1976), who used the lower test dose of 25 /ig of LH-RH found impaired or absent responses in 12 of their 17 women with hyperprolactinaemia.…”
Section: Discussionsupporting
confidence: 64%
“…How¬ ever, Glass et al (1976) detected only 3 pituitary tumours in their 13 hyper¬ prolactinaemic women but these were examined with lateral skull X-rays only, a possible explanation for the low incidence. This stresses the need of both antero-posterior and lateral X-ray projections of the sella turcica in women with amenorrhoea and several investigators also recommend routine tomo¬ graphy of the pituitary fossa of all women with hyperprolactinaemia (Vezina 8c Sutton 1974;Jacobs et al 1975;Nader et al 1976). …”
Section: Discussionmentioning
confidence: 99%
“…The published incidence of hyperprolactinemia in amenorrheic women varies between 13.4% and 20% . [24][25][26] The difference in rates is likely due to differences in assay methods or conditions under which sera are collected.…”
Section: Some Basic Considerationsmentioning
confidence: 99%